PERANAN PEMBELAJARAN MASYARAKAT TERHADAP PENGOLAHAN BIOGAS DI DESA LEREP KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Desi Susilowati (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2016)
The purpose of this research are to know 1) the learning activity of community in Lerep village (2) the roleof community learning on biogas processing. The population of this research has 36 processor and thesample has 30 processor. The Sampling use purposive sampling, the methods of this research useobservation method, questionnaire method and instrument in this research is observation sheet andquestionnaire sheet. The Analysis of data use percentage descriptif analysis. The learning activity in Lerep ishigh categorized, because at the time of learning, people writing the learning material about the biogasprocessing, reading material in the material guide books, listening tutor deliver his material and people alsoperform simulation of processing biogas. The biogas processing is high categorized, because the productionof biogas are appropriate with the right process. The government of village should work with othergovernment institute in the learning activities of community, so the learning can be increased , specially innonformal education.